2022
DOI: 10.3389/fresc.2022.905257
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological Management of Non-productive Chronic Cough in Adults: A Systematic Review

Abstract: BackgroundChronic cough is a common reason for medical referral and its prevalence is on the rise. With only one pharmaceutical therapy currently under review for the treatment of refractory chronic cough, exploring non-pharmacological chronic cough management therapies is important. This systematic review summarizes the effectiveness of non-pharmacological chronic cough therapies in adults with non-productive refractory chronic cough or cough due to chronic respiratory diseases.MethodsWe searched Medline, Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Chronic cough management includes pharmacological and non-pharmacological therapy. The effectiveness of pharmacological therapies is limited in refractory cough and unexplained cough [40,41]. Non-pharmacological therapy is effective for chronic cough with fewer side effects, whether alone or combined with pharmacological therapies, but there is a paucity of clinical data [2,42].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic cough management includes pharmacological and non-pharmacological therapy. The effectiveness of pharmacological therapies is limited in refractory cough and unexplained cough [40,41]. Non-pharmacological therapy is effective for chronic cough with fewer side effects, whether alone or combined with pharmacological therapies, but there is a paucity of clinical data [2,42].…”
Section: Discussionmentioning
confidence: 99%
“…Available treatments are mainly pharmacological, have limited effectiveness [ 44 , 45 ] and significant adverse effects, such as drowsiness and risk of addiction [ 46 ]. There is a paucity of evidence on non-pharmacological interventions in patients with chronic respiratory diseases, specifically in PF [ 47 ]. Observational and case studies have shown that multicomponent programmes consisting of education, vocal/laryngeal hygiene, hydration, cough control techniques, and psychoeducational counselling can help.…”
Section: Symptom Relief and Supportive Care End-of-life Carementioning
confidence: 99%
“…Therapy resulted in decreased objective cough counts, improvements in symptom scores and cough quality of life. A systematic review by Ilicic et al [ 21 ] reported that in comparison with control interventions, nonpharmacological therapy improves cough specific health related quality of life, as measured by the Leicester Cough Questionnaire (LCQ), by 1.53 points. This improvement is more than the minimally clinically important difference of 1.3 [ 22 ].…”
Section: Speech Pathology Treatment For Chronic Coughmentioning
confidence: 99%